2022
DOI: 10.3390/ijms232214375
|View full text |Cite
|
Sign up to set email alerts
|

MdPP2C24/37, Protein Phosphatase Type 2Cs from Apple, Interact with MdPYL2/12 to Negatively Regulate ABA Signaling in Transgenic Arabidopsis

Abstract: The phytohormone abscisic acid (ABA) plays an important role in the ability of plants to cope with drought stress. As core members of the ABA signaling pathway, protein phosphatase type 2Cs (PP2Cs) have been reported in many species. However, the functions of MdPP2Cs in apple (Malus domestica) are unclear. In this study, we identified two PP2C-encoding genes, MdPP2C24/37, with conserved PP2C catalytic domains, using sequence alignment. The nucleus-located MdPP2C24/37 genes were induced by ABA or mannitol in ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Melatonin is an important biological molecule that interacts with a variety of substances during plant development, especially to help regulate adaptive plant responses to abiotic stresses. Existing studies suggest that melatonin treatment can enhance plant salt tolerance in tomatoes [3], apples [4], barley [5], and rice [6]. Melatonin treatment mediates tolerance to salt in cotton by adjusting Ca 2+ and reactive oxygen scavenging mechanisms [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Melatonin is an important biological molecule that interacts with a variety of substances during plant development, especially to help regulate adaptive plant responses to abiotic stresses. Existing studies suggest that melatonin treatment can enhance plant salt tolerance in tomatoes [3], apples [4], barley [5], and rice [6]. Melatonin treatment mediates tolerance to salt in cotton by adjusting Ca 2+ and reactive oxygen scavenging mechanisms [7].…”
Section: Discussionmentioning
confidence: 99%
“…Saline soil is a source of extremely harmful abiotic stress, which prolongs the time of seed germination and plant maturation and reduces the rate of seed setting [4]. Per the data as of 2021, there are millions of hectares of saline soil in China, and the large quantities of soluble salts in saline soil far exceed the range that crops can bear, and the existence of saline soil seems to be more common than ever before [5]. Under salt stress, plant growth, carbon dioxide uptake, and light energy conversion and utilization are all constrained [6], and the diminishment of the electron transport rate and the imbalance of ion homeostasis are exhibited [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of this interaction, SnRK2 was autophosphorylated, and ABA response element-binding factors (ABFs) were activated ( Devireddy et al, 2021 ). The PYR/PYL protien plays a role in sensing and signaling ABA, MdPP2C24/37 from apple transgenic lines showed inhibited ABA-mediated stomatal closure, thus led to higher water loss rates ( Liu et al, 2022a ; Liu et al, 2022b ). In this study, thirteen PP2C genes were upregulated in leaves, eight ABF DEGs were downregulated in the leaves, two SNF1-related protein kinase 2 (SnRK2) were downregulated in roots to response the ABA accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that the cascade of MAPK induction by ABA regulates plant growth and development to improve plant drought tolerance. Liu et al (2022a) ; Liu et al (2022b) have shown ABA, ROS, and calcium ion (Ca 2+ ), played pivotal roles in controlling stomatal closure under drought conditions. In other words, H 2 O 2 was likely responsible for inducing RbohD overexpression, and OXI1 act as a response element for H 2 O 2 released from the respiratory burst, causing the expression of related genes by eliminating H 2 O 2 to maintain intracellular homeostasis ( Dietz, Turkan & Krieger-Liszkay, 2016 ).…”
Section: Discussionmentioning
confidence: 99%